Profiles of 14-3-3 and Total Tau in CSF Samples of Chinese Patients of Different Genetic Prion Diseases - Chen, Cao; Hu, Chao; Shi, Qi; Zhou, Wei; Xiao, Kang; Wang, Yuan; Liu, Lian; Chen, Jia; Xia, Ying; Dong, Xiao-Ping (Frontiers in Neuroscience, 2019)
Background: The abnormal alterations of proteins 14-3-3 and tau in cerebrospinal fluid (CSF) are widely used for the diagnosis of sporadic Creutzfeldt-Jakob disease (sCJD), while the situations of CSF biomarkers in genetic prion diseases (gPrDs), particularly in Chinese gPrDs patients, have not been well documented. Methods: Here with the help of commercial 14-3-3 and total tau ELISA kits, we evaluated the levels of proteins 14-3-3 and tau in the CSF samples of 140 Chinese patients of 14 different types of gPrDs. Results: We found that CSF 14-3-3 ELISA values in the patients with P102L GSS and D178N FFI were remarkably low, while those in the patients with T188K, E196A and E200K gCJD were relatively high. Linear correlation assays identified a well positive correlation between positive rate in Western blot and ELISA values of CSF 14-3-3. ELISA assays for total tau in CSF samples identified relatively high levels in the cases of D178N FFI, E196A and E200K gCJD, whereas relatively low levels in those of P102L GSS and T188K gCJD. Further assays showed that sCJD-associated abnormal changes in MRI appeared remarkable correlations with the elevation of CSF 14-3-3, while the patients with relatively short disease duration seemed to be associated with high level of CSF tau. Conclusions: These data illustrate heterogeneous profiles of CSF 14-3-3 and tau in various types of gPrDs, highly depending on the differences in the mutations in PRNP.